2009
DOI: 10.1073/pnas.0813177106
|View full text |Cite
|
Sign up to set email alerts
|

Trim24 targets endogenous p53 for degradation

Abstract: Numerous studies focus on the tumor suppressor p53 as a protector of genomic stability, mediator of cell cycle arrest and apoptosis, and target of mutation in 50% of all human cancers. The vast majority of information on p53, its protein-interaction partners and regulation, comes from studies of tumor-derived, cultured cells where p53 and its regulatory controls may be mutated or dysfunctional. To address regulation of endogenous p53 in normal cells, we created a mouse and stem cell model by knock-in (KI) of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(228 citation statements)
references
References 42 publications
8
220
0
Order By: Relevance
“…Aside from the observation that p53 can be degraded in MDM2-deficient mice, mutation of the known MDM2-targeted lysines on p53 does not prevent p53 ubiquitylation and degradation in cells (22). Moreover, several other E3 ligases, including another Trim family member, Trim24, are capable of promoting p53 degradation (23). An additional level of complexity stems from the ability of several of the p53-directed ligases to control each other's stability, potentially through direct interaction (24).…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the observation that p53 can be degraded in MDM2-deficient mice, mutation of the known MDM2-targeted lysines on p53 does not prevent p53 ubiquitylation and degradation in cells (22). Moreover, several other E3 ligases, including another Trim family member, Trim24, are capable of promoting p53 degradation (23). An additional level of complexity stems from the ability of several of the p53-directed ligases to control each other's stability, potentially through direct interaction (24).…”
Section: Resultsmentioning
confidence: 99%
“…Several new E3 ubiquitin ligases that promote degradation of p53 have been discovered, including Pirh2 (Leng et al 2003;Sheng et al 2008), Cop1 (Dornan et al 2004), TOPORS (Rajendra et al 2004), ARF-BP1 (Chen et al 2005), CARPs (Yang and El-Deiry 2007), and TRIM24 (Allton et al 2009;Tai and Benchimol 2009). The interaction pattern of Pirh2 with p53 is fundamentally different from that of MDM2 and MDMX.…”
Section: Targeting the P53 Pathway: Mdm2 Mdmx Sirtuins And Beyondmentioning
confidence: 99%
“…For example, Bonus is a homolog of TRIM 24, a p53 ligase in vertebrates. The results from loss-offunction studies indicated that Bonus is critical for maintaining p53 activity in Drosophila, suggesting that Bonus might be an evolutionarily conserved E3 ligase for p53 (14). The existence of multiple E3 ligases for p53 strongly suggests that specialization among them must be required for controlling p53 at multiple levels in different regulatory programs.…”
mentioning
confidence: 97%